Volume 2: Turbo Expo 2005 2005
DOI: 10.1115/gt2005-68907
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fuel Composition Effects in H2/CO/CH4 Mixtures Upon Lean Blowout

Abstract: This paper describes measurements of the dependence of lean blowout limits upon fuel composition for H2/CO/CH4 mixtures. Blowout limits were obtained at fixed approach flow velocity, reactant temperature, and combustor pressure at several conditions up to 4.4 atm and 470 K inlet reactants temperature. Consistent with prior studies, these results indicate that the percentage of H2 in the fuel dominates the mixture blowoff characteristics. That is, flames can be stabilized at lower equivalence ratios, adiabatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Hydrogen enrichment considerably extends the lean blowout limits of the methane fuel, and evidence of this is shown in Figure 4. These effects regarding the extension of lean blowout limits through hydrogen addition are consistent with the recent observations reported by [15,16,17]. In Figure 4a, a scaled LBO parameter 0.25 φ α , which is obtained empirically, is shown.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Hydrogen enrichment considerably extends the lean blowout limits of the methane fuel, and evidence of this is shown in Figure 4. These effects regarding the extension of lean blowout limits through hydrogen addition are consistent with the recent observations reported by [15,16,17]. In Figure 4a, a scaled LBO parameter 0.25 φ α , which is obtained empirically, is shown.…”
Section: Resultssupporting
confidence: 89%
“…In flamelet combustion regime blowout occurs when the local flame speed is less than the oncoming fluid velocity everywhere in the flame. Thus the stabilization mechanism for flamelet-like combustion is based on the flame front propagation [17]. Turbulent flame speed is often expressed in terms of laminar flame speed multiplied by a function which depends both on turbulence intensity and geometry.…”
Section: ( ) ( )mentioning
confidence: 99%
“…For the blended fuels, these properties were calculated using an algorithm by Zhang et al [12]. The Wobbe Index is used commercially as an indicator of fuel interchangeability and the range of values (Table I) for our fuels are equivalent to those from landfill gas to liquified petroleum gas.…”
Section: Experimental System and Diagnosticsmentioning
confidence: 99%
“…Another parameter that has been found to predict the LBO limit successfully is the Damkohler number. Zhang et al 160 reported an interesting finding that the LBO limit occurs at a Damkohler number of 0.4 for various fuel blends of H 2 /CO/CH 4 . Taamallah et al 74 presented a comprehensive review of syngas use in gas-turbine combustion.…”
Section: Fuel-flexible Premixed Oxy-fuel Combustionmentioning
confidence: 99%